A population in perpetual motion: Highly dynamic roosting behavior of a tropical island endemic bat. Issue 2 (11th February 2023) - Aguillon, Samantha; Le Minter, Gildas; Lebarbenchon, Camille; Hoarau, Axel O. G.; Toty, Céline; Joffrin, Léa; Ramanantsalama, Riana V.; Augros, Stéphane; Tortosa, Pablo; Mavingui, Patrick; Dietrich, Muriel
Abstract: Although island endemic bats are a source of considerable conservation concerns, their biology remains poorly known. Here, we studied the phenology and roosting behavior of a tropical island endemic species: the Reunion free‐tailed bat ( Mormopterus francoismoutoui ). This widespread and abundant species occupies various natural and anthropogenic environments such as caves and buildings. We set up fine‐scale monitoring of 19 roosts over 27 months in Reunion Island and analyzed roost size and composition, sexual and age‐associated segregation of individuals, as well as the reproductive phenology and body condition of individuals. Based on extensive data collected from 6721 individuals, we revealed a highly dynamic roosting behavior, with marked seasonal sex‐ratio variation, linked to distinct patterns of sexual aggregation among roosts. Despite the widespread presence of pregnant females all over the island, parturition was localized in a few roosts, and flying juveniles dispersed rapidly toward all studied roosts. Our data also suggested a 7‐month delay between mating and pregnancy, highlighting a likely long interruption of the reproductive cycle in this tropical bat. Altogether, our results suggest a complex social organization in the Reunion free‐tailed bat, with important sex‐specific seasonal and spatial movements, including the possibility of altitudinal migration. Bat tracking and genetic studies would provide additional insights into the behavioral strategies that shape the biology of this enigmatic bat species. The fine‐scale spatiotemporal data revealed by our study will serve to the delineation of effective conservation plans, especially in the context of growing urbanization and agriculture expansion in Reunion Island. Abstract : We studied the phenology and roosting behavior of a tropical island endemic species: Mormopterus francoismoutoui . We set up a fine‐scale monitoring of 19 roosts over 27 months in Reunion Island and collected extensive data from 6721 individuals. We revealed a highly dynamic roosting behavior, with marked seasonal sex‐ratio variation, linked to distinct patterns of sexual aggregation among roosts. Our study provides a relevant example of how dynamic are sex‐specific behavioral strategies in bats, even for tropical species living in small oceanic islands.